여성용 스키니 진의 브랜드별 패턴 특성 연구 - 오설영; Seol Young Oh; 서동애; Dong Ae Suh (The Research Journal of the Costume Culture, 2013)
In the 2010s, skinny jeans were trendy, and they became a must-have for young women. The styles, clothing pressure and buying behavior of skinny jeans have been studied, but the patternmaking of skinny jeans has not been researched yet. To analyze skinny jeans patterns, we grouped skinny jeans into nine brands. They were sorted into three groups: special jeans brand, trendy jeans brand, and SPA brand. This study compared skinny jeans` sizing systems, product dimensions and pattern measurements in three brand groups. The appearance and fit of skinny jeans were evaluated by random groups of people in their 20s and 30s. The sizing systems for skinny jeans were different with KS K0051, and they were shown waist girth in inches. The waist and hip circumferences were different among brand groups. In product dimensions, trendy jeans brands had a shorter crotch length, a lower crotch depth, a narrower back crotch width, and a longer inseam than the others. The measurements of skinny jeans flat patterns were significantly different in as below; front crotch depth, front crotch height, front crotch length, back crotch extension, gap between back and front crotch depth, back crotch height, back crotch length, and center back angle. In the sensory survey results, trendy jeans brands were evaluated well in the fit of the waist line, hip line, crotch line, midthigh line, outseam, inseam, side waist line, crotch length and overall fit.